Investigating the Influence of the Building Material on the Indoor Air Quality in Apartment in Dubai - Arar, Mohammad; Jung, Chuloh; Qassimi, Nahla Al (Frontiers in Built Environment, 2022)
The residents of Dubai spend more than 90% of their time indoors and this lifestyle makes them easily exposed to Sick Building Syndrome (SBS). Even though Dubai Municipality strictly apply the IAQ (Indoor Air Quality) stipulation, indiscreet use of unproven finishing materials has been increased to deteriorate the health of residents in Dubai. The objective of this paper is to investigate the degree of influence of building material on indoor air pollutants concentration by measurement and prediction. As a methodology, indoor pollutants concentration was measured and investigated, variables were extracted through emission intensity experiments, and the indoor concentration was predicted by applying the double exponential decay model. The result had shown that electronic products, furniture, and textile products become new sources of indoor air pollution. The difference in emission patterns of wallpaper and flooring is confirmed via the emission rate test. It is statistically proven that Formaldehyde (CH2O) and VOCs showed a difference in the cumulative emission amount within 100 hours but after that, it was confirmed that the difference in emission amount between materials became very small. In case of Formaldehyde (CH2O), the cumulative emission of the flooring material is greater than that of the wallpaper. This study will serve as a basic data to explore the cause of indoor air pollutants in daily life to reduce SBS symptoms in Dubai.